ANALYSIS OF PROFESSIONAL COMPETENCIES AND JOB SATISFACTION OF LIBRARIANS IN PRIVATE UNIVERSITIES IN SOUTH-WEST, NIGERIA - Oguntayo, S. A.; Unegbu, V. E.; Alegbeleye, G. O. (FUDMA Journal of Sciences, 2024)
The study analyzed the professional competencies and job satisfaction of librarians in private university libraries in South-West, Nigeria. A survey research design was used for the study. The participants in this study were two hundred and forty-three (243) librarians from thirty-three private universities in Nigeria's South-West. Total enumeration was used to cover the two hundred and forty-three (243) librarians working in the thirty-three under study. The researcher adopted the instrumentation of the questionnaire method from Yaya (2019) for the collection of data on job satisfaction.The response rate was 61.7%. Descriptive statistics of frequency, percentage, mean and standard deviation were used to analyze the research question. Findings revealed that librarians in private university libraries in South-West, Nigeria experienced a high level of job satisfaction in overall relationship with fellow workers, carrying support from colleagues, information sharing and team spirit among colleagues. Despite  high level of librarians’ job satisfaction; there was low satisfaction in the areas of salary and job security. Therefore, it is recommended that the management of private universities in the study areas improve satisfaction in these low areas. The librarians in the private university libraries in South-West, Nigeria possessed professional competence on the job. Professional competence was measured with three dimensions namely traits, knowledge and self-concept The study recommended that academic librarians’ professional competence on the job must be sustained.
Keywords: Librarians; Job Satisfaction; Private universities; Professional Competence; South-West; Nigeria